Peradaban Islam Dan Idelogi Politik Pada Masa Dinasti Mamluk Di Mesir - Abbas, St. Aisyah; Nisa, Akramun (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
elign="justify"The presence of the Mamluk dynasty in Messia, not only as a ruler, but also as a savior for the world and Islamic civilization, because this dynasty was able to defend its center of power from the attacks of the Mongols and defeat the Mongol army in Ayn Jalut under the leadership of Baybars (1260-1277) M), although this dynasty was a dynasty of slaves, who came from various tribes and nations, it was also able to create a military oligarchic order in foreign territory. These slave sultans asserted their control over the Syrian-Egyptian region, previously controlled by the crusaders. For some time they managed to hold back the attack of the Mongol troops led by Hulagu and Tamerlane. If they fail to survive, of course the entire historical and cultural order in West Asia and Egypt will change drastically. Thanks to their persistence, Egypt was able to survive, and survived the Mongol attacks that had destroyed Syria and Iraq at that time, so that the people of Egypt could still witness the continuity of culture and political institutions as a phenomenon that was not enjoyed by other Islamic countries outside the Arab mainland. . Since the construction of the city of Cairo, which began during the Fatimid dynasty in 969 AD, it has experienced three heydays, namely during the reign of Mu'iz Lidinillah of the Fatimid dynasty, during the nasty Ayyubid period under Salah al-Din al-Ayyubi, and under Baybars in Mamluk dynasty. Baybars again made the city of Cairo the most important center of Islamic civilization and culture. He restored city buildings, renovated al-Azhar. Thus the prestige of this city is increasing. Many buildings with beautiful architecture were built during the following Mamluk dynasty. The Mamluk dynasty experienced progress in various fields at that time, including; Political Sector, Government Sector, Science Sector, Art Sector, and Architecture and Development Sector and others. These advances were achieved thanks to the sultan's high personality and prestige, strong military solidarity, and the country's stability which was safe from disturbances.